Способ захоронения отработанного органического радиоактивного экстрагента - Гаврилов П. М. Петр Михайлович; Косарева И. М. Инесса Михайловна; Ананьев А. В. Алексей Владимирович; Савушкина М. К. Маргарита Константиновна; Федосеев А. М. Александр Михайлович; Хафизов Р. Р. Роберт Рафаэльевич; Поляков И. Е. Игорь Евгеньевич
опубл. 20.02.09